Leaf primordium size specifies leaf width and vein number among row‐type classes in barley. (19th June 2017) - Thirulogachandar, Venkatasubbu; Alqudah, Ahmad M.; Koppolu, Ravi; Rutten, Twan; Graner, Andreas; Hensel, Goetz; Kumlehn, Jochen; Bräutigam, Andrea; Sreenivasulu, Nese; Schnurbusch, Thorsten; Kuhlmann, Markus
Summary: Exploring genes with impact on yield‐related phenotypes is the preceding step to accomplishing crop improvements while facing a growing world population. A genome‐wide association scan on leaf blade area (LA) in a worldwide spring barley collection ( Hordeum vulgare L.), including 125 two‐ and 93 six‐rowed accessions, identified a gene encoding the homeobox transcription factor, Six‐rowed spike 1 (VRS1). VRS1 was previously described as a key domestication gene affecting spike development. Its mutation converts two‐rowed (wild‐type VRS1, only central fertile spikelets) into six‐rowed spikes (mutant vrs1, fully developed fertile central and lateral spikelets). Phenotypic analyses of mutant and wild‐type leaves revealed that mutants had an increased leaf width with more longitudinal veins. The observed significant increase of LA and leaf nitrogen (%) during pre‐anthesis development in vrs1 mutants also implies a link between wider leaf and grain number, which was validated from the association of vrs1 locus with wider leaf and grain number. Histological and gene expression analyses indicated that VRS1 might influence the size of leaf primordia by affecting cell proliferation of leaf primordial cells. This finding was supported by the transcriptome analysis of mutant and wild‐type leaf primordia where in the mutant transcriptional activation of genes related to cell proliferation was detectable. Here we show that VRS1 has an independent role on barley leaf development which might influence the grain number. Significance Statement: By applying a genome‐wide association study on leaf blade area (LA) in two‐ and six‐rowed spring barley ( Hordeum vulgare L.), homeobox transcription factor six‐rowed spike 1 (VRS1) was identified. Mutant studies, histological and gene expression analyses suggest that VRS1 influences the size of leaf primordia resulting in wider leaves with more longitudinal veins.